The Industrial Village Energy Approach: A Cost-Effective Approach To Balance Interests and Collaboratively Harness Onsite Solar Energy - Hebert, Lionel Michel Daniel (Curtin University, 2020)
While the residential sector has seen a strong and rapid uptake of photovoltaic panels on rooftops in the last decade, especially in Australia, the uptake has been much slower on commercial and industrial roofs. This research focuses on how commercial and industrial precincts can transition to cost-effective long-term solar energy generation in a manner that creates multiple benefits. The outcome is a new approach that benefits the energy customers, the embedded utility and the environment.